Government Intervention in Supervising Sale and Purchase Apartments Through Pre-Project Selling Systems in Indonesia - Dian Cahayani (Universitas Airlangga, 2020)
This study aims to determine the importance of government intervention to provide oversight of the sale and purchase apartments with a pre-project selling marketing system. This study uses a doctrinal legal research method that uses a statutory approach and a conceptual approach. The legal materials used are primary legal materials and secondary legal materials which are analyzed deductively and prescriptively. The results of the study explained that even though there had been regulations regarding the sale and purchase of apartments with a pre-project selling system, it turned out that in practice there were still many consumers who suffered losses.This was allegedly due to the absence of sanctions made by the government to overcome the fraudulent developers and the lack of government role in overseeing the process of buying and selling apartments with a pre-project selling system. So that government intervention is needed in buying and selling apartments with a pre-project selling system to meet the occupancy needs of the Indonesian people and protect Indonesian consumers.